Double-Layer Separate Ventricular Activation Patterns During Ventricular Tachycardia Associated With Myocarditis. (October 2016) - Yamada, Takumi; Lloyd, Steven G.; Yoshida, Naoki; Kay, G. Neal
Abstract : Supplemental Digital Content is available in the text.